E-Commerce and Consumer Apprehensions - Mahey, Ajay (Journal of Commerce and Trade, 2009)
E-commerce has quickly evolved since the 1990’s and now has a powerful presence in the Indian Economy. With thriving Indian websites and more than 49.4 million internet users in India, the e-commerce industry is growing with each passing day. However, consumers have numerous apprehensions with e-business—from payment issues, trustworthiness of sites, registration hassles to privacy issues. The paper is divided into four sections. The initial sections comprise the introduction and historical backdrop of e-commerce. These are followed by the section on growth of e-commerce in India which discusses the Indian usage data, Indian websites and e-tailing growth in India. The last section is on consumer apprehensions which discusses the points of views of buyers and sellers, demands of online consumers and understanding commerce schemes.